2020
DOI: 10.1080/14756366.2020.1838501
|View full text |Cite
|
Sign up to set email alerts
|

Activation of carbonic anhydrases from human brain by amino alcohol oxime ethers: towards human carbonic anhydrase VII selective activators

Abstract: The synthesis and carbonic anhydrase (CA; EC 4.2.1.1) activating effects of a series of oxime ether-based amino alcohols towards four human (h) CA isoforms expressed in human brain, hCA I, II, IV and VII, are described. Most investigated amino alcohol derivatives induced a consistent activation of the tested CAs, with K A s spanning from a low micromolar to a medium nanomolar range. Specifically, hCA II and VII, putative main CA targets when central nervous system (CNS) diseases are concerned, were most effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…These compounds are, therefore, of great interest in the field of neurodegenerative disorders treatment, where the levels of ROS are particular high. More recently, a large series of amino alcohol was reported by Nocentini et al obtained by ring opening of differently substituted epoxydic oxime ethers with isopropylamine or tert -butylamine [ 72 ]. These compounds were designed using as lead the β-amino alcohol timolol, previously found to act as CAA [ 73 ].…”
Section: Activation Studies On Human Casmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds are, therefore, of great interest in the field of neurodegenerative disorders treatment, where the levels of ROS are particular high. More recently, a large series of amino alcohol was reported by Nocentini et al obtained by ring opening of differently substituted epoxydic oxime ethers with isopropylamine or tert -butylamine [ 72 ]. These compounds were designed using as lead the β-amino alcohol timolol, previously found to act as CAA [ 73 ].…”
Section: Activation Studies On Human Casmentioning
confidence: 99%
“…The synthetized compounds were assayed as CAAs against four physiologically relevant hCA isoforms expressed in human brain, showing K A values spanning from the low micromolar to the medium nanomolar range. Compounds 64 and 65 in particular revealed to be highly selective for the isoform CA II and VII, respectively, opening new perspectives in the design of potent and selective CAAs based on the amino alcohol scaffold, as valid alternative to amines and amino acids [ 72 ] ( Figure 9 ).…”
Section: Activation Studies On Human Casmentioning
confidence: 99%
“…Due to the countless implications of CAs in biological processes, they are currently a validated drug target, with some molecules already marketed [ 32 ]; in fact, the development of activators [ 33 , 34 ] and inhibitors [ 28 , 35 , 36 ] of CAs is a hot topic in the medicinal chemistry area. There are several inhibition mechanisms [ 37 ], among which metal chelation (sulfonamides and their isosteric sulfamates, dithiocarbamates, hydroxamates), or entry blockade through prior CA-mediated transformations of the inhibitor (coumarins) are the most widely exploited.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the modulation of CAs activity through activators is less described than that by inhibitors; the latter is well documented for its relevance in the pharmacological field 20,42,[45][46][47][48] . Nevertheless, CAAs, such as D-phenylalanine and imidazole, have been recently proposed as neuroenhancement drugs possibly improving synaptic efficacy, spatial learning and memory 2,49 . Moreover, it has been demonstrated that CA levels are significantly decreased in the brain of patients with Alzheimer's disease (AD) 8,50 .…”
Section: Introductionmentioning
confidence: 99%
“…In analogy with what already done with other CAs classes from mammals and fungi 2,4,39,44,49,51,54,55 , we carried out an extensive study of the activation properties of amines and amino acids towards a member of the recently discovered group of i-CAs. To this purpose, we investigated the effect of these CAAs on an enzyme identified in the genome of the non-pathogenic Gram-negative bacterium Burkholderia territorii recovered from groundwater samples (acronym BteCAi) 56 .…”
Section: Introductionmentioning
confidence: 99%